2018
DOI: 10.1111/eci.13021
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus: Complex interplay of oxidative stress, cytokines, gastrointestinal motility and small intestinal bacterial overgrowth

Abstract: This study indicates that there is association between hyperglycaemia, oxidative stress (LPO), anti-oxidants (GSH, SOD and catalase), inflammatory cytokines, gut motility (OCTT), and small intestinal overgrowth in type 1 diabetes mellitus patients. This association is intensified as duration of disease increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…The evidence for SIBO in diabetes (T1D and T2D) seems more substantiated [44] with prevalence of SIBO ranging anywhere between 11.6% and 60% depending on the test performed [42,45]. This association comes off as intuitive as SIBO has been traditionally linked, at least partly, to a decrease in intestinal motility [45], intestinal transit, and autonomic neuropathy [46]. Although evidence for a connection between SIBO and intestinal permeability measured via dual sugar absorption test has been established in NAFLD [47] as well as immunodeficiency diseases [48], it remains unclear whether SIBO leads to increased permeability or whether both conditions have their roots in an additional common denominator.…”
Section: Quantitative Gut Microbiome Shifts In Metabolic Disease: Whementioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for SIBO in diabetes (T1D and T2D) seems more substantiated [44] with prevalence of SIBO ranging anywhere between 11.6% and 60% depending on the test performed [42,45]. This association comes off as intuitive as SIBO has been traditionally linked, at least partly, to a decrease in intestinal motility [45], intestinal transit, and autonomic neuropathy [46]. Although evidence for a connection between SIBO and intestinal permeability measured via dual sugar absorption test has been established in NAFLD [47] as well as immunodeficiency diseases [48], it remains unclear whether SIBO leads to increased permeability or whether both conditions have their roots in an additional common denominator.…”
Section: Quantitative Gut Microbiome Shifts In Metabolic Disease: Whementioning
confidence: 99%
“…This has been underlined in several studies pointing rather to a significant association between SIBO and nonalcoholic fatty liver disease [42], whereas the association between obesity and the risk of SIBO has been deemed insufficiently proven according to meta-analyses [43]. The evidence for SIBO in diabetes (T1D and T2D) seems more substantiated [44] with prevalence of SIBO ranging anywhere between 11.6% and 60% depending on the test performed [42,45]. This association comes off as intuitive as SIBO has been traditionally linked, at least partly, to a decrease in intestinal motility [45], intestinal transit, and autonomic neuropathy [46].…”
Section: Quantitative Gut Microbiome Shifts In Metabolic Disease: Whementioning
confidence: 99%
“…In the serum cytokine protein profile, the two main pro-inflammatory cytokines, TNF-α and IL-1β, decreased whereas the anti-inflammatory cytokines, IL-4 and IL-10, increased to values of the normoglycaemic controls in the same way as described for the therapy success after the combination with anti-TCR and anti-TNF-α in the rat model [25] and in the human situation [52]. High levels of IL-10 are considered to be important for long-term protection and preservation of β cell function [53] and T1D prevention [54]. Though not expressed in islets of control animals, serum levels of IL-17A and in particular of IL-6 were high in healthy control animals, providing evidence for the presence of sources in the organism other than the islets [44,55].…”
Section: Discussionmentioning
confidence: 58%
“…As a tradition, the Council of the European Society of Clinical Investigation (ESCI) will award at the next meeting in Bari, Italy (27‐29 May 2020), the best clinical research article published in the European Journal of Clinical Investigation (EJCI) from November 2018 to October 2019. In the final selection round, five outstanding articles were selected based on scientific impact, quality and novelty . Among the finalists, we read with interest the research article by Gomez‐Delgado et al , which was elected as the winner of the 2019 ESCI Award for the Best Clinical Basic Research Article.…”
mentioning
confidence: 99%
“…In the final selection round, five outstanding articles were selected based on scientific impact, quality and novelty. [1][2][3][4][5] Among the finalists, we read with interest the research article by Gomez-Delgado et al, 5 which was elected as the winner of the 2019 ESCI Award for the Best Clinical Basic Research Article. This study reported how Mediterranean diet (MedDiet) improved postprandial hypertriglyceridemia (ppHTG) in patients with coronary heart disease (CHD) carrying the apolipoproteins E (ApoE) rs 439401 single-nucleotide polymorphism (SNP) with the T allele.…”
mentioning
confidence: 99%